The Political Participation Issues in the 2024 Bantul Regent Election: Insights from Bawaslu - Alisa Novta; Amalia Istiqomah; Rayyan Dhika; Aisyah Arifaini; Fatkhan Akbar; Muhammad Mufadhol; Maftuh Rizqy; Selfa Khoirunnisa; Syahla Latifah (Universitas Negeri Yogyakarta, 2025)
This article delves into the troubling violations of political participation that unfolded during the 2024 Bantul Regent Election, viewed through the lens of the General Elections Supervisory Agency (Bawaslu). The study meticulously uncovers a range of infractions, including the insidious practice of vote buying, the alarming lack of impartiality among village officials, and the rampant spread of misinformation that has cast a shadow over public political engagement. Moreover, the research probes into the socio-economic dynamics and the intricate local power pressures that shape electoral participation, revealing a complex web of influences at play. The findings starkly illustrate how the involvement of officials in these violations and the prevalence of vote buying erode public trust in the very foundations of democracy. In light of these revelations, this article advocates for a robust strengthening of oversight, a commitment to political education, and a push for transparency in the electoral process, aiming to nurture a vibrant and cohesive form of political participation that truly reflects the will of the people.analyses socio-economic factors and local power pressures that influence participation. The results indicate that violations involving officials and the practice of vote buying reduce public trust in democratic mechanisms. This article recommends strengthening oversight, political education, and transparency of the election process to increase healthy and integrated political participation